X-ray tomography and modelling study on the mechanical behaviour and performance of metal foam flow-fields for polymer electrolyte fuel cells. (15th March 2019) - Fly, A.; Meyer, Q.; Whiteley, M.; Iacoviello, F.; Neville, T.; Shearing, P.R.; Brett, D.J.L.; Kim, C.; Chen, R.
Abstract: Porous metal foams have been used as alternative flow-fields in proton exchange membrane fuel cells (PEMFCs), exhibiting improved performance compared to conventional 'land and channel' designs. In the current work, the mechanical behaviour of PEMFCs using metal foam flow-fields is investigated across different length scales using a combination of electrochemical testing, X-ray computed tomography (CT), compression tests, and finite element analysis (FEA) numerical modelling. Fuel cell peak power was seen to improve by 42% when foam compression was increased from 20% to 70% due to a reduction in the interfacial contact resistance between the foam and GDL. X-ray CT scans at varying compression levels reveal high levels of interaction between the metal foam and gas diffusion layer (GDL), with foam ligaments penetrating over 50% of the GDL thickness under 25% cell compression. The interfacial contact area between the foam and GDL were seen to be 10 times higher than between the foam and a stainless-steel plate. Modelling results demonstrate highly uniform contact pressure distribution across the cell due to plastic deformation of the foam. The effect of stack over-tightening and operating conditions are investigated, demonstrating only small changes in load distribution when paired with a suitable sealing gasket material. Highlights: X-ray computed tomography of a PEMFC with metal foam flow-fields under compression. Intrusion of foam into GDL at high compression increases interfacial contact area. Structural 3D model of 5 cell PEMFC stack with metal foam flow fields introduced. Foam flow-field improves load distribution compared to land and channel design. Energy output has been increased as the compression of metal foam increased.